Coastal cultures of the long nineteenth century - Ingleby, Matthew; Kerr, Matthew P. M. (Matthew Peter Milton), 1982- (Edinburgh critical studies in Victorian culture., 2018)
This volume examines the cultural importance of the coastline in Britain during a time of vast change.